La théorie du Językowy Obraz Świata (Image Linguistique du Monde) : du monde universitaire polonais au contexte académique français - Kwapisz-Osadnik, Katarzyna; Collinet, Françoise (Studia Romanica Posnaniensia, 2022)
The paper proposes to link French (or Francophone) and Polish university didactics, in a context where their linguistic and cultural roots differ. The reflexion is based on the articulation of two theories: an object-theory (the Językowy Obraz Świata), which is borrowed from the field of polonistics, and an instrument-theory, (Perelman’s New Rhetoric). The didactic challenge is to propose a neo-rhetorical platform where prior agreements on concepts and theories are negotiated in order to finally raise students’ awareness of the problem of transfers of concepts and theories in the context of philological studies. These agreements must be made first within the same scientific community (Polish community), then between scientific communities representing different cultures (Polish and French communities).